An Antisense Pectin Methylesterase Gene Alters Pectin Chemistry and Soluble Solids in Tomato Fruit. - Tieman, DM (1992)
Pectin methylesterase (PME, EC 3.1.11) demethoxylates pectins and is believed to be involved in degradation of pectic cell wall components by polygalacturonase in ripening tomato fruit. We have introduced antisense and sense chimeric PME genes into tomato to elucidate the role of PME in fruit development and ripening. Fruits from transgenic plants expressing high levels of antisense PME RNA showed <10% of wild-type PME enzyme activity and undetectable levels of PME protein and mRNA. Lower PME enzyme activity in fruits from transgenic plants was associated with an increased molecular weight and methylesterification of pectins and decreased levels of total and chelator soluble polyuronides in cell walls. The fruits of transgenic plants also contained higher levels of soluble solids than wild-type fruits. This trait was maintained in subsequent generations and segregated in normal Mendelian fashion with the antisense PME gene. These results indicate that reduction in PME enzyme activity in ripening tomato fruits had a marked influence on fruit pectin metabolism and increased the soluble solids content of fruits, but did not interfere with the ripening process.